Purine and non-purine xanthine oxidase inhibitors: today and perspectives in the management of gout - Detyukova, K. D. (Запорізький державний медико-фармацевтичний університет, 2024)
Aim: to provide a comparative analysis of modern urate-lowering therapy with xanthine oxidase inhibitors in the context of their effectiveness and safety.
Keywords: тези доповідей